العمل الخيري في المجتمع الإماراتي: دراسة في واقعة ومؤسساتة - مزروعي، هند سعيد نصيب سعيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This current study highlights the situation of charitable work in the Emirati society. The study focuses factors of the media, governmental support, and the work and living conditions of workers in the region. The study examined samples of volunteers at Sharjah Charity International, and Al-Ehsan Charity Association. This study came as a result of increasing the activities of charitable sector in the Emirati society. This study is considered an analytical descriptive as it describes the phenomena and analyses dimensions of charitable work in the Emirati society. It also analyses the situation of the country through the laws and the personal initiatives as well as influences of the media and the human situation in some countries in the region on the charitable work. This study relied on the quantitative method (Survey), where, the researcher used the statistical processing of the collected data and apply it to the statistical system (SPSS). The current study reached a number of results: 1.The varieties of activities in the Emirati charitable sector. 2.The governmental support which is considered the most important factor of reinforcing the charitable work in the Emirati society. 3.The importance of media in general, and the social media specifically of supporting the activities of charitable work recently. 4.The influence of the charitable sector in the Emirati society in relation to the human and living situation within the region.